A post cardiac surgery home-monitoring system - Georghiou, Georgios P.; Lambrinou, Ekaterini; Matheou, George; Kyriacou, Efthyvoulos C.; Chimonidou, Panayiota; Pattichis, Constantinos S.; Barberis, Vassilis I. I. (My University, 2011)
The aim of this work was to develop a system that will be used for remote monitoring of patients at home after a cardiac surgery so as to keep their rehabilitation period as smooth as possible and avoid unnecessary visits to the hospital. The developed system is an integrated web-based system which can regularly monitor several biosignals like ECG (3 - 12 leads), Oxygen Saturation, Non Invasive Blood Pressure, and additional parameters like body weight. The system has been completed and tested and is now under the evaluation phase from healthy volunteers and cardiac patients.
Keywords: Biosignals; Cardiac surgery; Home monitoring; Telemedicine